Unifying Theories of Programming Second International Symposium, UTP 2008, Dublin, Ireland, September 8-10, 2008, Revised Selected Papers - Butterfield, Andrew; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the thoroughly refereed post-proceedings of the Second International Symposium on Unifying Theories of Programming, UTP 2008, held at Trinity College, Dublin, Ireland, in September 2008. The 15 revised full papers presented, together with two invited talks, were carefully reviewed and selected from 20 submissions. Based on the pioneering work on unifying theories of programming of Tony Hoare, He Jifeng, and others, the aims of this Symposium series are to continue to reaffirm the significance of the ongoing UTP project, to encourage efforts to advance it by providing a focus for the sharing of results by those already actively contributing, and to raise awareness of the benefits of such a unifying theoretical framework among the wider computer science and software engineering communities.
Refinement Calculus as a Theory of Contracts (Invited Paper) -- Transaction Calculus -- UTP and Temporal Logic Model Checking -- A Note on Traces Refinement and the conf Relation in the Unifying Theories of Programming -- Reasoning about Loops in Total and General Correctness -- Lazy UTP -- Monadic Maps and Folds for Multirelations in an Allegory -- Unifying Theories of Interrupts -- UTP Semantics for Handel-C -- Unifying Theories of Locations -- Unifying Input Output Conformance -- The Miracle of Reactive Programming -- Encoding Circus Programs in ProofPowerZ -- Component Publications and Compositions -- Denotational Approach to an Event-Driven System-Level Language.
Keywords: Computer science; Software engineering; Logic design; Artificial intelligence; Computer Science; Logics and Meanings of Programs; Software Engineering; Programming Languages, Compilers, Interpreters; Mathematical Logic and Formal Languages; Programming Techniques; Artificial Intelligence (incl. Robotics).